Flora of the Montero Sector, Chira Island, Costa Rica: diversity, Uses, and Sustainable Ecotourism - Bonilla Villalobos, Verónica (2025)
Chira Island, located in the Gulf of Nicoya, Costa Rica, hosts a representative ecosystem of the tropical dry forest, characterized by marked seasonality and plant biodiversity adapted to water stress conditions. This study was conducted in 2023 and aimed to inventory the plant species present along the Montero trail, to create a guide that promotes sustainable tourism and environmental education within the local community. The methodology was based on a systematic survey along a 562.09-meter trail, recording species within a 10-meter range on both sides of the path. Taxonomic identification was carried out using specialized botanical literature and consultation of scientific databases. A total of 83 plant species were identified, belonging to 77 genera and 38 families of angiosperms. The most represented families were Fabaceae and Malvaceae, consistent with the typical structure of tropical dry forests. Trees predominated (59%), followed by shrubs (18%), herbaceous plants (15%), and vines (6%). Additionally, 91% of the species were native, while 9% were naturalized or exotic. These results highlight the ecological importance of the study area and its potential for the development of conservation strategies, ecological restoration, and sustainable tourism. The relevance of ecotourism initiatives based on local biodiversity is emphasized, integrating interpretive trails and educational programs that strengthen the conservation of natural resources and the socio-economic well-being of the community.